Science Teachers Perceptions of the Nature of Science (NOS) and the Nature of Scientific Inquiry (NOSI) - Al-Qoyyim, Thufail Mujaddid; Amanah, Prelia Dwi; Muliati, Eka; Fitratunisyah, Fitratunisyah; Jauhari, Muhammad Tantawi; Jufri, A Wahab (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to analyze science teachers' perceptions of the Nature of Science (NOS) and Nature of Scientific Inquiry (NOSI), including their understanding of the nature of scientific knowledge, the scientific method, and the challenges in its implementation in the classroom. A survey method was employed, involving 61 science teachers from various educational levels. The findings reveal that 59% of teachers agreed and 34.4% strongly agreed that they understand the nature of science and apply it in their teaching. Additionally, 65.6% agreed and 26.2% strongly agreed that scientific knowledge is tentative and continually evolving. Regarding the scientific method, 49.2% agreed and 44.2% strongly agreed that science is based on empirical evidence and can be tested. However, despite a general understanding of the importance of inquiry-based approaches, 47.5% disagreed and 14.8% strongly disagreed with the effectiveness of the inquiry model in science education, indicating significant challenges in its implementation. Factors such as limited facilities, time constraints, and students' readiness were identified as key obstacles to the optimal integration of NOS and NOSI. Therefore, enhanced teacher training, infrastructure support, and more adaptable teaching strategies are essential to ensure the effective implementation of NOS and NOSI in science education.